La producción audiovisual como recurso informativo de diversidad de género en jóvenes con el Consejo Cantonal para la Protección de Derechos Ambato - Miranda Vásconez, Camila Anahí (2024)
In this project, an exhaustive investigation has been carried out about diversity and gender ideologies in Ambato in young people between 15 and 24 years old, affecting the relationship with people who belong to gender minorities. To address this problem comprehensively, a combined qualitative and quantitative approach has been used, which allows us to understand and analyze the reality of knowledge about gender diversity in young people. This has given guidelines for carrying out strategies regarding audiovisual production in order to show reality and inform about this topic to be discussed, complementing with the contribution of professionals in these areas both in gender issues and in audiovisual production. Thus carrying out research to ensure the effectiveness of the project with a simple and impactful approach that could be used as support resources for future generations.